Empathy in adolescents, cognitions and affect during the pandemic, Peru - Ledesma Pérez, Fernando (2023)
The objective of the research was to carry out an analysis of the capacity for empathy in 178 adolescents from 14 to 17 years of age who are in the last cycle of Regular Basic Education. The convergent design was applied. In the first stage, a checklist was applied, and in the second, a semi-structured interview. The synchronous-descriptive cross-sectional study made possible to report that the adolescent, during the pandemic, is empathetic, aware of the possibility of becoming infected, believes that his/her care and self-protection will prevent him/ her from becoming infected, suffers with the pain of others who accompanies.